If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(0) + 4y = 0 Multiply 5 * 0 0 + 4y = 0 Anything times zero is zero. 0 + 4y = 0 Remove the zero: 4y = 0 Solving 4y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '4'. y = 0 Simplifying y = 0
| 3x+0.8x=90 | | x^2+2x+7x+14=0 | | x^4-7x^3-6x^2= | | -3b+6=-4b-10 | | 5x+9+2x=23 | | 3x^2-8x+7=0 | | 3.5=3.5+0.076x | | 4.5x-5.4=2.7x | | 5x+4(-4)=0 | | 4=p+2 | | x-2=6-3x | | x-5y=12 | | 2p=10.2 | | 3(2x+5)=6x+5 | | 5-(x+3)=-x+2 | | 12.85=y+4 | | -4x+(-1)=5 | | c-1.86=6.7 | | 3a^2-13a=-14 | | -4x+1=5 | | q-3=1 | | -4-0=5 | | y+9.59=19.59 | | 12x+11=10x+17 | | 6x-9=6(x-6) | | -4x+0=5 | | 2(4x-1)=8x-2 | | 0.6x+4=0.2x+5 | | 5x+9=x+69 | | 3(2x+2)+5x=2(4x-1)-2(-x+1) | | 8a^2-18=0 | | 5+18z=35z^2 |